Rubidium and cesium ion adsorption material as well as preparation method and application thereof
By combining modified metal ferrocyanide adsorbent with polyvinyl alcohol and crosslinked sodium alginate, a stable framework is formed using a silane coupling agent, which solves the problem of poor stability of the adsorbent and achieves efficient rubidium and cesium adsorption and material stability.
Patent Information
- Application Number
- CN202311315051.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-11
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-10-11
AI Technical Summary
The existing polyvinyl alcohol skeleton granulation products have poor stability in the wrapping of adsorbent powder, resulting in agglomeration of adsorbents and are unable to be effectively applied to fixed bed equipment.
The stability of the adsorbent is improved by using an organic sulfate and/or an organic sulfonate modified metal ferrocyanide adsorbent, forming a skeleton with polyvinyl alcohol and crosslinked sodium alginate, and being connected by an amino group-containing silane coupling agent.
The long-term stability of the adsorbent is achieved, avoided shedding, and maintained high saturated adsorption capacity of rubidium and cesium, while improving the mechanical strength and hydrophilicity of the material.
Smart Images

Figure BDA0004490214460000091 
Figure BDA0004490214460000161 
Figure BDA0004490214460000171
Abstract
Description
Technical Field
[0001] The present invention relates to the field of adsorption materials, and in particular to a rubidium-cesium ion adsorption material and a preparation method and application thereof. Background Art
[0002] Rubidium and cesium are rare alkali metals with important economic value and application value in emerging industries, including biomedical research, solar cells, atomic clocks and electronic products. Rubidium and cesium are mainly extracted from ores or salt lakes as cesium or lithium. The rarity of rubidium and cesium and their specific industrial uses make it necessary to develop efficient processes to extract rubidium and cesium. Researchers use solvent extraction, precipitation, adsorption and hybrid membrane adsorption techniques to recover Rb.
[0003] The adsorption method for extracting rubidium and cesium ions from the solution has the advantages of high recovery rate and simple operation. Metal ferrocyanide adsorbent has good ion exchange performance and large adsorption capacity, but its powder particles are fine and its mechanical strength is poor, so it cannot be directly applied to conventional equipment such as fixed beds for adsorption-desorption. Therefore, it is urgent to develop a granulation product with good mechanical strength and high adsorption capacity. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of poor stability of adsorbent powder wrapping and agglomeration of adsorbent powder in existing granulation products using polyvinyl alcohol as a skeleton, and to provide a rubidium-cesium ion adsorption material. In the rubidium-cesium ion adsorption material, the metal ferrocyanide adsorbent modified by organic sulfate and / or organic sulfonate can be connected with the polyvinyl alcohol and cross-linked sodium alginate forming the skeleton through an amino-containing silane coupling agent, and the metal ferrocyanide adsorbent is not easy to fall off during long-term use, and the metal ferrocyanide adsorbent modified by organic sulfate and / or organic sulfonate has excellent compatibility with the polyvinyl alcohol and cross-linked sodium alginate as the skeleton, so that the rubidium-cesium ion adsorption material has excellent stability while maintaining a high saturated adsorption capacity of rubidium and cesium.
[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a rubidium-cesium ion adsorption material, wherein the rubidium-cesium ion adsorption material comprises a skeleton and a metal ferrocyanide adsorbent modified by an organic sulfonate and / or an organic sulfate dispersed in the skeleton;
[0006] The skeleton comprises polyvinyl alcohol and cross-linked sodium alginate; the skeleton is connected with the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate via an amino-containing silane coupling agent.
[0007] A second aspect of the present invention provides a method for preparing a rubidium-cesium ion adsorption material, wherein the preparation method comprises the following steps:
[0008] (1) mixing and modifying a metal ferrocyanide adsorbent with an organic sulfonate aqueous solution and / or an organic sulfate aqueous solution to obtain a metal ferrocyanide adsorbent modified with an organic sulfonate and / or an organic sulfate;
[0009] (2) mixing a metal ferrocyanide adsorbent modified by an organic sulfonate and / or organic sulfate, a polyvinyl alcohol aqueous solution and a sodium alginate aqueous solution, adjusting the pH value, and then adding an optional pore-forming agent and an amino-containing silane coupling agent to carry out a coupling reaction;
[0010] (3) Adding the product of step (2) into a multivalent cation salt solution to obtain the rubidium-cesium ion adsorption material.
[0011] The third aspect of the present invention provides a rubidium-cesium ion adsorption material prepared by the above preparation method.
[0012] A fourth aspect of the present invention provides a use of the above-mentioned rubidium-cesium ion adsorption material in the field of extracting rubidium and / or cesium.
[0013] Through the above technical scheme, the rubidium-cesium ion adsorption material provided by the present invention and its preparation method and application obtain the following beneficial effects:
[0014] The metal ferrocyanide adsorbent modified by organic sulfate and / or organic sulfonate in the rubidium-cesium ion adsorption material of the present invention can be connected with the polyvinyl alcohol and cross-linked sodium alginate forming a skeleton through an amino-containing silane coupling agent. During long-term use, the metal ferrocyanide adsorbent is not easy to fall off, and the metal ferrocyanide adsorbent modified by organic sulfate and / or organic sulfonate has excellent compatibility with the polyvinyl alcohol and cross-linked sodium alginate serving as a skeleton, so that the rubidium-cesium ion adsorption material has excellent stability while maintaining a high saturated adsorption capacity of rubidium and cesium.
[0015] The preparation method of the rubidium-cesium ion adsorption material provided by the present invention comprises the following steps: a metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, polyvinyl alcohol, cross-linked sodium alginate and an amino-containing silane coupling agent are used for coupling reaction; during long-term use, the obtained rubidium-cesium ion adsorption material has a high saturated adsorption capacity and excellent stability, and the metal ferrocyanide adsorbent is not easy to fall off. DETAILED DESCRIPTION
[0016] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0017] The first aspect of the present invention provides a rubidium-cesium ion adsorption material, wherein the rubidium-cesium ion adsorption material comprises a skeleton and a metal ferrocyanide adsorbent modified by an organic sulfonate and / or an organic sulfate dispersed in the skeleton;
[0018] The skeleton comprises polyvinyl alcohol and cross-linked sodium alginate; the skeleton is connected with the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate via an amino-containing silane coupling agent.
[0019] In the present invention, the metal ferrocyanide adsorbent modified by organic sulfate and / or organic sulfonate in the rubidium-cesium ion adsorption material can be connected with the polyvinyl alcohol and cross-linked sodium alginate forming a skeleton through an amino-containing silane coupling agent. During long-term use, the metal ferrocyanide adsorbent is not easy to fall off, and the metal ferrocyanide adsorbent modified by organic sulfate and / or organic sulfonate has excellent compatibility with the polyvinyl alcohol and cross-linked sodium alginate serving as a skeleton, so that the rubidium-cesium ion adsorption material has excellent stability while maintaining a high saturated adsorption capacity of rubidium and cesium.
[0020] According to the present invention, based on the total weight of the rubidium-cesium ion adsorption material, the content of the polyvinyl alcohol is 5wt%-16wt%, the content of the cross-linked sodium alginate is 3wt%-8wt%, the content of the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate is 25wt%-65wt%, and the content of the amino-containing silane coupling agent is 15wt%-65wt%.
[0021] In the present invention, based on the total weight of the rubidium-cesium ion adsorbent material, the sum of the content of the polyvinyl alcohol, the cross-linked sodium alginate, the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate, and the amino-containing silane coupling agent is 100wt%. When the content of each component in the rubidium-cesium ion adsorbent material meets the above range, the strength of the adsorbent material can be ensured, the adsorbent material can be prevented from being broken during adsorption-desorption, and the adsorbent material can be ensured to have a larger adsorption capacity.
[0022] Furthermore, based on the total weight of the rubidium-cesium ion adsorption material, the content of the polyvinyl alcohol is 8wt%-12wt%, the content of the cross-linked sodium alginate is 4wt%-6wt%, the content of the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate is 30wt%-50wt%, and the content of the amino-containing silane coupling agent is 35wt%-55wt%.
[0023] In the present invention, the organic sulfonate and / or organic sulfate can form a modified layer on the surface of the metal ferrocyanide adsorbent. The modified layer can make the metal ferrocyanide adsorbent have good compatibility with the polymer skeleton and avoid agglomeration of metal ferrocyanide in the polymer.
[0024] According to the present invention, the thickness of the modified layer formed by the organic sulfonate and / or organic sulfate in the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate is 4-10 nm.
[0025] According to the present invention, the organic sulfonate is sodium methyl ester sulfonate (MES).
[0026] In the present invention, there is no particular limitation on the number of carbon atoms in the sodium fatty acid methyl ester sulfonate. For example, the sodium fatty acid methyl ester sulfonate may be C12-C18 sodium fatty acid methyl ester sulfonate.
[0027] According to the present invention, the organic sulfate is sodium fatty alcohol polyoxyethylene ether sulfate (AES).
[0028] According to the present invention, the metal ferrocyanide adsorbent is selected from at least one of ferric ferrocyanide, potassium cobalt ferrocyanide, potassium nickel ferrocyanide, potassium titanium ferrocyanide, potassium copper ferrocyanide and potassium cadmium ferrocyanide.
[0029] Furthermore, the metal ferrocyanide adsorbent is ferric ferrocyanide.
[0030] According to the present invention, the amino-containing silane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.
[0031] In the present invention, when the above-mentioned amino-containing silane coupling agent is selected, the polymer skeleton can be better cross-linked, so that the rubidium-cesium ion adsorption material is formed and has better strength and is not damaged during use.
[0032] Furthermore, the amino-containing silane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.
[0033] According to the present invention, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol.
[0034] In the present invention, when the weight average molecular weight of the polyvinyl alcohol satisfies the above range, the strength of the rubidium-cesium ion adsorbent is higher.
[0035] Furthermore, the weight average molecular weight of the polyvinyl alcohol is 80,000-110,000 g / mol.
[0036] According to the present invention, the alcoholysis degree of the polyvinyl alcohol is 85-98%.
[0037] In the present invention, when the alcoholysis degree of polyvinyl alcohol satisfies the above range, the mechanical strength and hydrophilicity of the adsorbent material can be improved.
[0038] According to the present invention, the average particle size of the rubidium-cesium ion adsorption material is 2-5 mm.
[0039] According to the present invention, the porosity of the rubidium-cesium ion adsorption material is 75-85%.
[0040] In the present invention, when the porosity of the rubidium-cesium ion adsorption material meets the above range, it means that the skeleton formed by polyvinyl alcohol and cross-linked sodium alginate has a network structure, which can reduce the mass transfer resistance and enable the rubidium-cesium ion adsorption material to have a faster water mass transfer rate.
[0041] Furthermore, the porosity of the rubidium-cesium ion adsorption material is 80-85%.
[0042] According to the present invention, the contact angle of the rubidium-cesium ion adsorption material is 30-45°.
[0043] In the present invention, when the contact angle of the rubidium-cesium ion adsorbent satisfies the above range, it indicates that the rubidium-cesium ion adsorbent has excellent hydrophilicity.
[0044] A second aspect of the present invention provides a method for preparing a rubidium-cesium ion adsorption material, wherein the preparation method comprises the following steps:
[0045] (1) mixing and modifying a metal ferrocyanide adsorbent with an organic sulfonate aqueous solution and / or an organic sulfate aqueous solution to obtain a metal ferrocyanide adsorbent modified with an organic sulfonate and / or an organic sulfate;
[0046] (2) mixing a metal ferrocyanide adsorbent modified by an organic sulfonate and / or organic sulfate, a polyvinyl alcohol aqueous solution and a sodium alginate aqueous solution, adjusting the pH value, and then adding an optional pore-forming agent and an amino-containing silane coupling agent to carry out a coupling reaction;
[0047] (3) Adding the product of step (2) into a multivalent cation salt solution to obtain the rubidium-cesium ion adsorption material.
[0048] In the present invention, a metal ferrocyanide adsorbent modified by an organic sulfonate and / or an organic sulfate, polyvinyl alcohol, cross-linked sodium alginate and an amino-containing silane coupling agent are used for coupling reaction, and the obtained rubidium-cesium ion adsorbent has high saturated adsorption capacity and excellent stability during long-term use, and the metal ferrocyanide adsorbent is not easy to fall off.
[0049] According to the present invention, the metal ferrocyanide adsorbent is selected from at least one of ferric ferrocyanide, potassium cobalt ferrocyanide, potassium nickel ferrocyanide, potassium titanium ferrocyanide, potassium copper ferrocyanide and potassium cadmium ferrocyanide.
[0050] Furthermore, the metal ferrocyanide adsorbent is ferric ferrocyanide.
[0051] According to the present invention, the organic sulfonate is sodium fatty acid methyl ester sulfonate.
[0052] According to the present invention, the organic sulfate is sodium fatty alcohol polyoxyethylene ether sulfate.
[0053] According to the present invention, the concentrations of the organic sulfonate aqueous solution and the organic sulfate aqueous solution are independently 0.1 mg / L-1 mg / L.
[0054] According to the present invention, the mass ratio of the metal ferrocyanide adsorbent to the organic sulfonate and / or organic sulfate is 1:0.1-1.
[0055] According to the present invention, the mixed modification conditions include: modification time of 1-4h, modification temperature of 25-40°C.
[0056] According to the present invention, based on the total weight of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol is 5wt%-16wt%, the content of the cross-linked sodium alginate is 3wt%-8wt%, the content of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate is 25wt%-65wt%, and the content of the amino-containing silane coupling agent is 15wt%-65wt%.
[0057] In the present invention, the sum of the content of the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate, the polyvinyl alcohol, the sodium alginate and the amino-containing silane coupling agent is 100wt%. When the content of each component meets the above range, the prepared rubidium and cesium ion adsorption material has both good strength and large adsorption capacity.
[0058] Furthermore, based on the total weight of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol is 8wt%-12wt%, the content of the cross-linked sodium alginate is 4wt%-6wt%, the content of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate is 30wt%-50wt%, and the content of the amino-containing silane coupling agent is 35wt%-55wt%.
[0059] According to the present invention, the concentration of the polyvinyl alcohol aqueous solution is 10wt%-15wt%.
[0060] According to the present invention, the amino-containing silane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.
[0061] In the present invention, when the above-mentioned amino-containing silane coupling agent is selected, the polymer skeleton can be better cross-linked, so that the rubidium-cesium ion adsorption material is formed and has better strength, and is not damaged during use.
[0062] Furthermore, the amino-containing silane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane.
[0063] According to the present invention, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol.
[0064] In the present invention, when the weight average molecular weight of the polyvinyl alcohol satisfies the above range, the strength of the rubidium-cesium ion adsorbent is higher.
[0065] Furthermore, the weight average molecular weight of the polyvinyl alcohol is 80,000-110,000 g / mol.
[0066] According to the present invention, the alcoholysis degree of the polyvinyl alcohol is 85-98%.
[0067] In the present invention, when the alcoholysis degree of polyvinyl alcohol satisfies the above range, the mechanical strength and hydrophilicity of the adsorbent material can be improved.
[0068] In the present invention, the pore-forming agent is hydrogen peroxide.
[0069] According to the present invention, the amount of the pore former is 1 wt%-12 wt% relative to the weight of the polyvinyl alcohol.
[0070] According to a preferred embodiment of the present invention, in step (2), after mixing the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, the polyvinyl alcohol aqueous solution and the sodium alginate aqueous solution, adjusting the pH value, adding the amino-containing silane coupling agent for coupling reaction, and adding the pore-forming agent after the coupling reaction is carried out for a time T; a better pore-forming effect can be obtained. Preferably, the coupling reaction is carried out for a time T ≥ 30 min.
[0071] According to the present invention, in step (2), the pH value is 1-3.
[0072] According to the present invention, the coupling reaction conditions include: the coupling reaction temperature is 50-70° C., and the coupling reaction time is 50 min-4 h.
[0073] According to the present invention, in step (3), the multivalent cation salt solution is selected from at least one of a CaCl2 aqueous solution, a MgCl2 aqueous solution and a CuCl2 aqueous solution.
[0074] Furthermore, the multivalent cation salt solution is a CaCl2 aqueous solution.
[0075] According to the present invention, the amount of the multivalent cation salt solution is such that the mass ratio of sodium alginate to the multivalent cation salt is 1:1-4.
[0076] According to the present invention, the concentration of the multivalent cation salt solution is 1wt%-4wt%.
[0077] According to the present invention, the product of step (2) is dripped into the multivalent cation salt solution at a speed of 1-2 mL / min.
[0078] In the present invention, the step (1) comprises: mixing and modifying the metal ferrocyanide adsorbent with an organic sulfonate aqueous solution and / or an organic sulfate aqueous solution, and centrifuging and drying to obtain a metal ferrocyanide adsorbent modified with an organic sulfonate and / or an organic sulfate.
[0079] The third aspect of the present invention provides a rubidium-cesium ion adsorption material prepared by the above preparation method.
[0080] A fourth aspect of the present invention provides a use of the above-mentioned rubidium-cesium ion adsorption material in the field of extracting rubidium and / or cesium.
[0081] The present invention will be described in detail below through examples.
[0082] In the following examples and comparative examples, the properties involved are obtained by the following methods:
[0083] Dynamic adsorption and desorption cycle method of rubidium-cesium ion adsorbent material: The obtained rubidium-cesium ion adsorbent material (4 g) was placed in a glass column for acid washing (using 400 mL of 0.5 M hydrochloric acid at 30°C, the hydrochloric acid flow rate was 2 mL / min), and then 400 mL of rubidium carbonate solution (RbCO3) was pumped into the column at a flow rate of 2 mL / min using a peristaltic pump. + concentration of 200ppm, pH = 10) or 400mL cesium carbonate solution (cesium carbonate Cs 2+ The concentration is 50ppm, pH=7.6), and the dynamic adsorption-desorption cycle is carried out for 24 hours. Then, 0.5M hydrochloric acid (200mL) is pumped in at a flow rate of 2mL / min with a peristaltic pump, and the rubidium ions or cesium ions in the particles are desorbed for 24 hours. Then, the particles are washed with deionized water until neutral, which is one cycle.
[0084] Saturated adsorption capacity of rubidium and cesium ions: Monitor the change of adsorption capacity over time during a dynamic adsorption-desorption cycle and calculate the saturated adsorption capacity Q. The calculation formula is as follows:
[0085]
[0086] Wherein, Q is the saturated adsorption capacity, in mg / g, which reflects the adsorption amount of the rubidium-cesium ion adsorption material when the adsorption reaches equilibrium; C0 and C are the initial and saturated ion concentrations in the solution, in mg / L, respectively; V is the volume of the rubidium carbonate solution or the cesium carbonate solution, in L; M is the mass of the rubidium-cesium ion adsorption material, in g.
[0087] Concentrations of rubidium ions and cesium ions: Ion concentrations were measured using ion chromatography (ICS-1100, DIONEX, America).
[0088] Contact angle of rubidium-cesium ion adsorption material: The contact angle was tested using the DSA100 surface contact angle measuring instrument produced by KRUSS, Germany.
[0089] Porosity of rubidium-cesium ion adsorption material: The porosity is measured using a porosity tester.
[0090] Mass loss ratio of rubidium-cesium ion adsorption material: the weighing method is adopted, that is, the mass of the adsorption material before use (i.e., the initial mass) and the mass of the adsorption material after 30 adsorption-desorption cycles are weighed respectively, and the ratio of the lost mass to the initial mass is the mass loss ratio.
[0091] In the rubidium-cesium ion adsorption material, the contents of polyvinyl alcohol, cross-linked sodium alginate, metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, and amino-containing silane coupling agent are calculated by the corresponding raw material feed ratio.
[0092] Average particle size of the rubidium-cesium ion adsorbing material and thickness of the modified layer: The thickness of the modified layer formed by the organic sulfonate and / or organic sulfate and the average particle size of the rubidium-cesium ion adsorbing material were characterized by scanning electron microscopy (SEM, S-4800).
[0093] The weight average molecular weight of polyvinyl alcohol is measured by gel permeation chromatography (GPC).
[0094] Polyvinyl alcohol A: the alcoholysis degree is 88%, and the weight average molecular weight is 89000 g / mol.
[0095] Polyvinyl alcohol B: alcoholysis degree is 95%, and weight average molecular weight is 12000 g / mol.
[0096] In the following examples and comparative examples, the room temperature is 25°C.
[0097] Other raw materials used in the preparation examples, embodiments and comparative examples are all commercially available.
[0098] Preparation Example 1
[0099] Ferric ferrocyanide was dispersed in an aqueous solution, and an AES aqueous solution (wherein the concentration of AES was 0.1 wt%) was added and mixed so that the mass ratio of the adsorbent powder and AES was 1:0.1, and the mixture was mixed and modified at room temperature for 2 h.
[0100] The mixed solution was centrifuged and the solid phase material was dried to obtain an organic sulfate-modified metal ferrocyanide adsorbent A. The water content of the adsorbent was 0.5 wt%.
[0101] Preparation Example 2
[0102] Ferric ferrocyanide was dispersed in an aqueous solution, and an AES aqueous solution (wherein the concentration of AES was 0.1 wt%) was added and mixed so that the mass ratio of the adsorbent powder to the AES was 1:0.5, and the mixture was mixed and modified at room temperature for 2 h.
[0103] The mixed solution was centrifuged and the solid phase material was dried to obtain an organic sulfate-modified metal ferrocyanide adsorbent B, the water content of which was 0.5 wt %.
[0104] Preparation Example 3
[0105] Ferric ferrocyanide was dispersed in an aqueous solution, and an AES aqueous solution (wherein the concentration of AES was 0.1 wt%) was added and mixed so that the mass ratio of the adsorbent powder and AES was 1:1, and the mixture was mixed and modified at room temperature for 2 h.
[0106] The mixed solution was centrifuged and the solid phase material was dried to obtain an organic sulfate-modified metal ferrocyanide adsorbent C. The water content of the adsorbent C was 0.5 wt%.
[0107] Preparation Example 4
[0108] The organic sulfonate-modified metal ferrocyanide adsorbent D was prepared according to the method of Preparation Example 1, except that the AES aqueous solution was replaced by an MES aqueous solution. The organic sulfonate-modified metal ferrocyanide adsorbent D had a water content of 0.5 wt %.
[0109] Example 1
[0110] (1) A 15 wt% aqueous solution of polyvinyl alcohol A, an organic sulfate-modified metal ferrocyanide adsorbent A and an aqueous solution of sodium alginate (1 wt%) were mixed and stirred uniformly. After adjusting the pH to 1 with 0.1 M HCl, the mixture was stirred uniformly at 70° C., and γ-aminopropyltrimethoxysilane was added. Based on the total weight of the organic sulfate-modified metal ferrocyanide adsorbent, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol was 8.7 wt%, the content of the cross-linked sodium alginate was 4.4 wt%, the content of the organic sulfate-modified metal ferrocyanide adsorbent was 34.7 wt%, and the content of the amino-containing silane coupling agent was 52.2 wt%. The mixture was coupled at 70° C. for 2 h, and 1 mL of 1 wt% H2O2 solution was added after the coupling reaction was carried out for 30 min (the amount of the pore-forming agent was 6.7 wt% relative to the weight of the polyvinyl alcohol).
[0111] (2) The product obtained in step (1) is loaded into a syringe pump and dripped into a 4 wt % CaCl2 aqueous solution at a rate of 1 mL / min. After drying, a rubidium-cesium ion adsorption material with a particle size of 3 mm is obtained.
[0112] Example 2
[0113] (1) A 15 wt % aqueous solution of polyvinyl alcohol A, an organic sulfate modified metal ferrocyanide adsorbent B and an aqueous solution of sodium alginate (1 wt %) were mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1 M HCl, the mixture was stirred uniformly at 70° C., and γ-aminopropyltrimethoxysilane was added. Based on the total weight of the organic sulfate modified metal ferrocyanide adsorbent, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol was 11.8 wt %, the content of the cross-linked sodium alginate was 5.9 wt %, the content of the organic sulfate modified metal ferrocyanide adsorbent was 47.1 wt %, and the content of the amino-containing silane coupling agent was 35.2 wt %. The mixture was coupled at 70° C. for 2 h, and 1 mL of 1 wt % H2O2 solution was added after the coupling reaction was carried out for 30 min (the amount of the pore-forming agent was 6.7 wt % relative to the weight of the polyvinyl alcohol).
[0114] (2) The product obtained in step (1) is loaded into a syringe pump and dripped into a 4 wt % CaCl2 aqueous solution at a rate of 1 mL / min. After drying, a rubidium-cesium ion adsorption material with a particle size of 3 mm is obtained.
[0115] Example 3
[0116] (1) A 15 wt % aqueous solution of polyvinyl alcohol A, an organic sulfate modified metal ferrocyanide adsorbent C and an aqueous solution of sodium alginate (1 wt %) were mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1 M HCl, the mixture was stirred uniformly at 70° C., and γ-aminopropyltrimethoxysilane was added. Based on the total weight of the organic sulfate modified metal ferrocyanide adsorbent, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol was 6.9 wt %, the content of the cross-linked sodium alginate was 3.5 wt %, the content of the organic sulfate modified metal ferrocyanide adsorbent was 27.5 wt %, and the content of the amino-containing silane coupling agent was 62.1 wt %. The mixture was coupled at 70° C. for 2 h, and 1 mL of 1 wt % H2O2 solution was added after the coupling reaction was carried out for 30 min (the amount of the pore-forming agent was 6.7 wt % relative to the weight of the polyvinyl alcohol).
[0117] (2) The product obtained in step (1) is loaded into a syringe pump and dripped into a 4 wt % CaCl2 aqueous solution at a rate of 1 mL / min. After drying, a rubidium-cesium ion adsorption material with a particle size of 3 mm is obtained.
[0118] Example 4
[0119] The rubidium-cesium ion adsorbent material was prepared according to the method of Example 1, except that the metal ferrocyanide adsorbent A modified by organic sulfate was replaced by the metal ferrocyanide adsorbent D modified by organic sulfonate.
[0120] Example 5
[0121] The rubidium and cesium ion adsorption material was prepared according to the method of Example 1, except that γ-aminopropyltrimethoxysilane was replaced by γ-aminopropyltriethoxysilane.
[0122] Example 6
[0123] The rubidium and cesium ion adsorption material was prepared according to the method of Example 1, except that γ-aminopropyltrimethoxysilane was replaced by 4-amino-3,3-dimethylbutyltrimethoxysilane.
[0124] Example 7
[0125] (1) A 15 wt % aqueous solution of polyvinyl alcohol A, an organic sulfate modified metal ferrocyanide adsorbent A and an aqueous solution of sodium alginate (1 wt %) were mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1 M HCl, the mixture was stirred uniformly at 70° C., and γ-aminopropyltrimethoxysilane was added. Based on the total weight of the organic sulfate modified metal ferrocyanide adsorbent, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol was 15.4 wt %, the content of the cross-linked sodium alginate was 7.7 wt %, the content of the organic sulfate modified metal ferrocyanide adsorbent was 61.5 wt %, and the content of the amino-containing silane coupling agent was 15.4 wt %. The mixture was coupled at 70° C. for 2 h, and 1 mL of 1 wt % H2O2 solution was added after the coupling reaction was carried out for 30 min (the amount of the pore-forming agent was 6.7 wt % relative to the weight of the polyvinyl alcohol).
[0126] (2) The product obtained in step (1) is loaded into a syringe pump and dripped into a 4 wt % CaCl2 aqueous solution at a rate of 1 mL / min. After drying, a rubidium-cesium ion adsorption material with a particle size of 3 mm is obtained.
[0127] Example 8
[0128] (1) A 9wt% aqueous solution of polyvinyl alcohol B, an organic sulfate-modified metal ferrocyanide adsorbent A and an aqueous solution of sodium alginate (1wt%) were mixed and stirred uniformly, and after adjusting the pH to 1 with 0.1M HCl, the mixture was stirred uniformly at 70°C, and γ-aminopropyltrimethoxysilane was added. Based on the total weight of the organic sulfate-modified metal ferrocyanide adsorbent, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol was 8.7wt%, the content of the cross-linked sodium alginate was 4.4wt%, the content of the organic sulfate-modified metal ferrocyanide adsorbent was 34.7wt%, and the content of the amino-containing silane coupling agent was 52.2wt%. The mixture was coupled at 70°C for 2h, and 1mL of 1wt% H2O2 solution was added after the coupling reaction was carried out for 30min (the amount of the pore-forming agent was 11.1wt% relative to the weight of the polyvinyl alcohol).
[0129] (2) The product obtained in step (1) is loaded into a syringe pump and dripped into a 4 wt % CaCl2 aqueous solution at a rate of 1 mL / min. After drying, a rubidium-cesium ion adsorption material with a particle size of 3 mm is obtained.
[0130] Example 9
[0131] A rubidium and cesium ion adsorption material was prepared according to the method of Example 1, except that the content of the polyvinyl alcohol was 15.2 wt %, the content of the cross-linked sodium alginate was 7.6 wt %, the content of the organic sulfate-modified metal ferrocyanide adsorbent was 75.7 wt %, and the content of the amino-containing silane coupling agent was 1.5 wt %.
[0132] Example 10
[0133] (1) A 15 wt % aqueous solution of polyvinyl alcohol A, an organic sulfate modified metal ferrocyanide adsorbent A and a sodium alginate aqueous solution (1 wt %) were mixed and stirred uniformly. After adjusting the pH to 1 with 0.1 M HCl, the mixture was stirred uniformly at 70° C., γ-aminopropyltrimethoxysilane and 1 mL of 1 wt % H2O2 solution (the amount of the pore-forming agent was 6.7 wt % relative to the weight of the polyvinyl alcohol) were added, and coupling was carried out at 70° C. for 2 h. Based on the total weight of the organic sulfate modified metal ferrocyanide adsorbent, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol was 8.7 wt %, the content of the cross-linked sodium alginate was 4.4 wt %, the content of the organic sulfate modified metal ferrocyanide adsorbent was 34.7 wt %, and the content of the amino-containing silane coupling agent was 52.2 wt %.
[0134] (2) The product obtained in step (1) is loaded into a syringe pump and dripped into a 4 wt % CaCl2 aqueous solution at a rate of 1 mL / min. After drying, a rubidium-cesium ion adsorption material with a particle size of 3 mm is obtained.
[0135] Embodiment 11
[0136] The rubidium-cesium ion adsorption material was prepared according to the method of Example 1, except that no H2O2 solution was added.
[0137] Comparative Example 1
[0138] The rubidium and cesium ion adsorption material was prepared according to the method of Example 1, except that the organic sulfate-modified metal ferrocyanide adsorbent A was replaced with ferric ferrocyanide. Based on the total weight of ferric ferrocyanide, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of polyvinyl alcohol was 8.7wt%, the content of cross-linked sodium alginate was 4.4wt%, the content of ferric ferrocyanide was 34.7wt%, and the content of amino-containing silane coupling agent was 52.2wt%.
[0139] Comparative Example 2
[0140] The rubidium-cesium ion adsorbent material was prepared according to the method of Example 1, except that the amino-containing silane coupling agent was not added. Based on the total weight of the organic sulfate-modified metal ferrocyanide adsorbent, polyvinyl alcohol and sodium alginate, the content of the polyvinyl alcohol was 18.2wt%, the content of the cross-linked sodium alginate was 9.1wt%, and the content of the organic sulfate-modified metal ferrocyanide adsorbent was 72.7wt%.
[0141] Comparative Example 3
[0142] The rubidium-cesium ion adsorption material was prepared according to the method of Example 1, except that sodium alginate was not added.
[0143] In the present invention, the contents of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent in the rubidium-cesium ion adsorption materials of the embodiments and comparative examples are shown in Table 1. Thickness, porosity, contact angle, saturated adsorption capacity Q of the modified layer of the rubidium-cesium ion adsorption materials of the embodiments and comparative examples Rb , cesium ion saturation adsorption capacity Q Cs The mass loss ratios are shown in Table 2.
[0144] Table 1
[0145]
[0146]
[0147] Table 2
[0148]
[0149] It can be seen from the results that the rubidium cesium ion adsorption capacity of the rubidium cesium ion adsorption material of the embodiment of the present application is greater than or equal to 10.2 mg / g, and the cesium ion saturation adsorption capacity is greater than or equal to 5 mg / g. The rubidium cesium ion adsorption material is adsorbed and acid-washed and desorbed, and the mass loss ratio is less than or equal to 2.1wt% after 30 times of repetition; it shows that the rubidium cesium ion adsorption material prepared by the scheme of the present invention has a good rubidium ion and cesium ion saturation adsorption capacity, and at the same time, the structure of the rubidium cesium ion adsorption material is stable, and the metal ferrocyanide adsorbent is not easy to fall off from the skeleton after long-term use, and has good acid resistance. Comparative Example 3 does not add sodium alginate, and polyvinyl alcohol has poor formability in CaCl2 aqueous solution.
[0150] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A rubidium-cesium ion adsorption material, characterized in that: The rubidium-cesium ion adsorption material comprises a skeleton and a metal ferrocyanide adsorbent modified by an organic sulfonate and / or an organic sulfate dispersed in the skeleton; The skeleton comprises polyvinyl alcohol and cross-linked sodium alginate; The framework is connected to the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate via an amino-containing silane coupling agent.
2. The rubidium-cesium ion adsorbent according to claim 1, wherein: Based on the total weight of the rubidium-cesium ion adsorbent material, the content of the polyvinyl alcohol is 5wt%-16wt%, the content of the cross-linked sodium alginate is 3wt%-8wt%, the content of the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate is 25wt%-65wt%, and the content of the amino-containing silane coupling agent is 15wt%-65wt%; Preferably, based on the total weight of the rubidium-cesium ion adsorption material, the content of the polyvinyl alcohol is 8wt%-12wt%, the content of the cross-linked sodium alginate is 4wt%-6wt%, the content of the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate is 30wt%-50wt%, and the content of the amino-containing silane coupling agent is 35wt%-55wt%.
3. The rubidium-cesium ion adsorbent according to claim 1 or 2, wherein: The thickness of the modified layer formed by the organic sulfonate and / or organic sulfate in the metal ferrocyanide adsorbent modified by the organic sulfonate and / or organic sulfate is 4-10 nm; Preferably, the organic sulfonate is sodium fatty acid methyl ester sulfonate; Preferably, the organic sulfate is sodium fatty alcohol polyoxyethylene ether sulfate; Preferably, the metal ferrocyanide adsorbent is selected from at least one of ferric ferrocyanide, potassium cobalt ferrocyanide, potassium nickel ferrocyanide, potassium titanium ferrocyanide, potassium copper ferrocyanide and potassium cadmium ferrocyanide.
4. The rubidium-cesium ion adsorption material according to any one of claims 1 to 3, wherein: The amino-containing silane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane; Preferably, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol; Preferably, the alcoholysis degree of the polyvinyl alcohol is 85-98%.
5. The rubidium-cesium ion adsorption material according to any one of claims 1 to 4, wherein: The average particle size of the rubidium-cesium ion adsorption material is 2-5 mm; Preferably, the porosity of the rubidium-cesium ion adsorption material is 75-85%, preferably 80-85%; Preferably, the contact angle of the rubidium-cesium ion adsorption material is 30-45°.
6. A method for preparing a rubidium-cesium ion adsorption material, characterized in that: The preparation method comprises the following steps: (1) mixing and modifying a metal ferrocyanide adsorbent with an organic sulfonate aqueous solution and / or an organic sulfate aqueous solution to obtain a metal ferrocyanide adsorbent modified with an organic sulfonate and / or an organic sulfate; (2) mixing a metal ferrocyanide adsorbent modified by an organic sulfonate and / or organic sulfate, a polyvinyl alcohol aqueous solution and a sodium alginate aqueous solution, adjusting the pH value, and then adding an optional pore-forming agent and an amino-containing silane coupling agent to carry out a coupling reaction; (3) Adding the product of step (2) into a multivalent cation salt solution to obtain the rubidium-cesium ion adsorption material.
7. The preparation method according to claim 6, wherein: The metal ferrocyanide adsorbent is selected from at least one of ferric ferrocyanide, potassium cobalt ferrocyanide, potassium nickel ferrocyanide, potassium titanium ferrocyanide, potassium copper ferrocyanide and potassium cadmium ferrocyanide; Preferably, the organic sulfonate is sodium fatty acid methyl ester sulfonate; Preferably, the organic sulfate is sodium fatty alcohol polyoxyethylene ether sulfate; Preferably, the concentrations of the organic sulfonate aqueous solution and the organic sulfate aqueous solution are independently 0.1 mg / L-1 mg / L; Preferably, the mass ratio of the metal ferrocyanide adsorbent to the organic sulfonate and / or organic sulfate is 1:0.1-1; Preferably, the mixed modification conditions include: modification time of 1-4h, and modification temperature of 25-40°C.
8. The preparation method according to claim 6 or 7, wherein: Based on the total weight of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of the polyvinyl alcohol is 5wt%-16wt%, the content of the cross-linked sodium alginate is 3wt%-8wt%, the content of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate is 25wt%-65wt%, and the content of the amino-containing silane coupling agent is 15wt%-65wt%; Preferably, based on the total weight of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate, polyvinyl alcohol, sodium alginate and amino-containing silane coupling agent, the content of polyvinyl alcohol is 8wt%-12wt%, the content of the cross-linked sodium alginate is 4wt%-6wt%, the content of the metal ferrocyanide adsorbent modified by organic sulfonate and / or organic sulfate is 30wt%-50wt%, and the content of the amino-containing silane coupling agent is 35wt%-55wt%; Preferably, the concentration of the polyvinyl alcohol aqueous solution is 10wt%-15wt%; Preferably, the amino-containing silane coupling agent is selected from at least one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldimethoxysilane, methylaminopropyltrimethoxysilane and 4-amino-3,3-dimethylbutyltrimethoxysilane; Preferably, the weight average molecular weight of the polyvinyl alcohol is 80,000-150,000 g / mol; Preferably, the alcoholysis degree of the polyvinyl alcohol is 85-98%; Preferably, the amount of the pore former is 1 wt%-12 wt% relative to the weight of the polyvinyl alcohol.
9. The preparation method according to any one of claims 6 to 8, wherein: In step (2), the pH value is 1-3; Preferably, the coupling reaction conditions include: the coupling reaction temperature is 50-70° C., and the coupling reaction time is 50 min-4 h.
10. The preparation method according to any one of claims 6 to 9, wherein: In step (3), the polyvalent cation salt solution is selected from at least one of a CaCl2 aqueous solution, a MgCl2 aqueous solution and a CuCl2 aqueous solution; Preferably, the amount of the multivalent cation salt solution is such that the mass ratio of sodium alginate to the multivalent cation salt is 1:1-4; Preferably, the concentration of the multivalent cation salt solution is 1wt%-4wt%; Preferably, the product of step (2) is dripped into the multivalent cation salt solution at a rate of 1-2 mL / min.
11. A rubidium-cesium ion adsorption material prepared by the preparation method according to any one of claims 6 to 10.
12. Use of the rubidium-cesium ion adsorption material according to any one of claims 1 to 5 and 11 in the field of extracting rubidium and / or cesium.
Citation Information
Patent Citations
Polyving alcohol composite hydrogel and preparation method thereof
CN103665685A
Attapulgite-polyacrylic acid nanocomposite gel with high adsorptivity and preparation method thereof
CN106582564A
Large-scale preparation method of high-stability caesium removing adsorbent, product of preparation method and application of product
CN108160048A
Adsorption material based on modified sodium alginate microspheres and preparation method and application of material
CN110170311A
Preparation method of metal ferricyanide adsorbent particles for liquid rubidium and cesium resource extraction
CN113509910A
Cited By
Fibrous rubidium adsorbent as well as preparation method and application thereof
CN121198250A